Frequency of H.Pylori in Liver Cirrhosis Patients with Overt Hepatic Encephalopathy: A Cross-Sectional Study Design - Zabihullah, Shaista Alam, Aurangzaib Khan, Munaza Khattak, Zabihullah, Shabir Ahmed Orakzai, Siyab Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The study aim is to evaluate the frequency of H. pylori in Liver cirrhosis patients with overt HE. Place and duration of study: This Study is conducted in the department of Pathology, Peshawar Institute of Medical Sciences (PIMS) Peshawar and The duration of study is from Ist April, 2022 till 30th September, 2022. Material and Method: Cross sectional study design having sample size of 140 individuals suffering from H.pylori infections also having a history of hepatic insufficiency.Non-probability sampling technique is used, Patients having age greater than 30 years of any sex but having an history of hepatic cirrhosis for the last 5-6 months, ultrasounds for overt Hepatic encephalopathy are included in this study design. Sample participants having different age strata, disease duration and child’s pugh classification are expressed in means and standard deviation with the help of SPSS. Results: Patients having helicobacter pylori infection in hepatic cirrohsis with overt hepatic encephalopathy are 44(31.4%) and 96 (68.4%) patients have not suffering from any simultaneous infection. There are 65(46.4%) males and 75(53.6% ) females, The mean duration of disease in our study is 4.89+ 1.5 years. Stratification with duration of disease in years in shown in table 1, having significant result with p-value of 0.000. Startified findings of CP is found to be insignificant with H.Pylori infection(p-value=0.500). Practical Implications: According to this study, H pylori infection should be promptly assessed in all patients with liver cirrhosis. The patients' chances of developing hepatic encephalopathy and bleeding chances as a result of the H pylori infection. It may be possible to lessen the severity of consequences such bleeding from esophageal varices, portal hypertensive gastropathy, and hepatic encephalopathy with the early identification and subsequent eradication of H pylori infection. Conclusion: The conclusive remarks of this study shows the prevalence of less frequency of Helicobacter pylori infections in Liver cirrhosis in the patients of Pakistan. But, among all of them Helicobacter Pylori causes prolongation in duration of liver cirrhosis. This study also highlights that as aged patients with liver cirrhosis having more cases of having helicobacter pylori infection. Keywords: Hepatic Encephalopathy, Child’s Pugh Classification,Helicobacter Pylori infection, Liver insufficiency